Coping self-efficacy, pre-competitive anxiety, and subjective performance among athletes - Nicholls, A. R.; Polman, R.; Levy, A. R. (European Journal of Sport Science, 2010)
The aim of this study was to explore the relationships between (a) coping self-efficacy and subjective performance, (b) coping self-efficacy and pre-competitive anxiety, and (c) pre-competitive anxiety and subjective performance. Participants were 307 athletes (252 males, 55 females) aged 16-34 years (mean age 21.3 years, s = 2.8) who competed at national/international (n = 18), county (n = 54), club/university (n = 139), and beginner (n = 96) level. All participants completed a measure of coping self-efficacy and anxiety before a competitive event and a subjective performance measure after competing. Our findings revealed that there was a significant and positive relationship between coping self-efficacy and subjective performance. Negative relationships between coping self-efficacy and both somatic and cognitive anxiety were also observed. However, somatic and cognitive anxiety did not predict subjective performance. The present findings support previous results regarding the influence of self-efficacy and provide applied practitioners with recommendations that may enhance athletic performance, via improving the coping self-efficacy beliefs of their clients.